Effect of Distance Education via Short Message Service of Mobile Phones on Self-efficacy and HbA1C of Patients with type 2 Diabetes Mellitus - mandana goodarzi; mohammadreza Sarmadi; nasim saeed (Zanjan University of Medical Sciences and Health Services, 2015)
Background and Objectives: Mobile-based education as the most basic form of e-health initiatives can be an important aspect to be considered and valued for providing health services. This study assessed the effect of education via short message service on hemoglobin A1C and self-efficacy among patients with type 2 diabetes. Materials and Methods: This was a randomized clinical trial in which 81 patients with type 2 diabetes were selected based on the inclusion criteria and were randomly allocated into two experimental (n=43) and control (n=38) groups. The experimental group received educational messages. Data were measured at baseline and three months after the intervention. Data were analyzed using the Fisher's exact test, t-test and ANCOVA in the SPSS-17. Results: The hemoglobin A1C (p<0.001) and self-efficacy (p=0.024) were significantly different between the control and experimental groups after the intervention. Conclusion: Our findings indicated a favorable effect of an educational intervention using the mobile phone capabilities. Using digital communication technology in the field of health care delivery and management of health are recommended to change individuals' behavior.